Validation of logical models for the management of tuberculosis treatment - Shirley Ribeiro dos Santos Linhares; Elisabete Pimenta Araújo Paz; Gisela Cordeiro Pereira Cardoso (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to describe the steps of validation of the logical models of the Directly Observed Treatment and the Information System of the Directly Observed Treatment Short-Course Strategy. Methods: methodological study carried out from February to June 2018, in two stages. The content of the items that make up the models was based on scientific evidence and submitted to the experts for content validation. The Content Validity Index was applied, accepting the value ≥ 0.80. Results: the agreement, regarding its validity, was satisfactory in the 79 items analyzed. The logical models were considered valid with a Global Validity Index of 0.91 for the Directly Observed Treatment and 0.87 for the Information System. Conclusions: the logical models were considered valid in terms of content, being a useful and timely instrument to support managers in decision-making.